Grand Challenges and the MBA. (June 2023) - Shantz, Amanda; Sayer, Melissa; Byrne, Janice; Dempsey-Brench, Kiera
Humanity is facing multiple grand challenges, compelling a myriad of diverse actors to interact, coordinate, and collaborate like never before. Business schools have a role to play in equipping future leaders to tackle them and we posit that to do so, leaders must be able to take multiple perspectives into consideration and look to the future while being morally aware. We carry out an in-depth audit of how MBA programs currently fare in this regard. We find that despite the urgency and salience of these transnational and intractable issues, little attention is paid to preparing MBA students to address grand challenges. We identify three barriers that may prevent educators from facilitating student acquisition of these competencies and conclude by proposing potential models of MBA programs for grand challenges.